Responding to public disclosure of corporate social irresponsibility in host countries: Information control and ownership control - Wang, Stephanie Lu; Li, Dan (Journal of International Business Studies, 2019)
We extend the internalization literature by theorizing on how public disclosure of corporate social irresponsibility (CSI) can damage reputation-based firm-specific advantages of multinational companies (MNCs) and how foreign subsidiary governance can subsequently be used as strategic responses. Specifically, we distinguish between two foreign subsidiary governance mechanisms – information control and ownership control – that the prior literature has often assumed operate in parallel, and posit that they function in divergent directions in this context. Furthermore, we explain how two host-country characteristics – press freedom and regulatory quality – amplify the need for MNCs to utilize different governance mechanisms as responses to CSI disclosure.